TINJAUAN VISUAL POSTER POLANDIA - Farid Abdullah (Jurnal Dimensi Seni Rupa dan Desain, 2008)
AbstractOver the past millennium, by the lSth century the Poland nobles democracy had gradual! y dech"ned into anarchy. The culture of Poland is close! y connected with its intricate 1000 year dynamic hts"tory. Poland was known for being the centre of "wall and board " art, including poster. The artist of Poland always been hospitable and eager to follow cultural and artistic trends in other countries. In 2Oth centuries the Poll`ish poster artist focus on cultural advancement, often took precedence over poh"tical and economic activity. These factors have contributed to the versatile nature of Pollish poster with all its complex nuances. AbstrakMelewati era millennium, pada abad ke 18, kehidupan de- mokrasi di Polandia mengalami perubahan besar dari kemapanan ke arah tindakan anarkis. Secara umum, kebudaya-an Polandia berkait erat dengan sejarah kehidupannya yang dinamis selama kurang lebih 1000 tahun. Dibelahan Eropa Timur, Polandia juga dikenal juga sebagai negeri "Seni dinding dan papan pengumuman". Seniman- seniman Polandia sangat terbuka dan berhasrat besar untuk mengikuti perkembangan budaya dan kecenderungan artistik di negara-negara lain. Memasuki abad ke-20, para seniman poster Polandia memilih fokus pada pengembangan kebudayaan setempat, terkadang terlibat pada aktifitas politik